Analysis of Service Quality in Access by KAI Application Using E-ServQual Method and Root Cause Analysis (RCA) - Maulida Dewi Amanda; Dwi Sukma Donoriyanto (2477 - 6165, 2025)
Access by KAI is an official application by PT. Kereta Api Indonesia which is expected to facilitate users in managing their train tickets. Access by KAI hasn’t been able to meet the user’s expectations, which can be seen from the application rating of 2.4/5.0 and the majority of the 210,637 reviews gave the lowest rating, this shows user dissatisfaction with the quality of service provided in the Access by KAI. Therefore, this study aims to analyze the quality of Access by KAI services from the user’s perspective as a reference for providing improvement proposals to improve the quality of services. This research uses the E-ServQual method to identify quality attributes that need improvement and the Root Cause Analysis (RCA) method to propose solutions for enhancing service quality within the application. Based on the results of calculations and analysis, 10 attributes need to be improved service quality because they are negative (-). These negative attributes cause user dissatisfaction while using the application so there are suggestions for improvement from the root causes of problems in quality of service of these attributes.